Challenges in mental health nursing: current opinion - Sabella D; Fay-Hillier T (Dove Medical Press, 2014)
Donna Sabella, Theresa Fay-Hillier College of Nursing and Health Professions, Drexel University, Philadelphia, PA, USA Abstract: The current mental health care system in the US continues to struggle with providing adequate care and services to all that require it due to limited resources, biases from both other professions and the public, and the complexities of treatment of many of those individuals or populations that suffer from mental illness. Mental health nurses, also referred to as psychiatric nurses, are impacted by those same biases, limited resources, and complexities in their role. This paper provides a brief history of mental health nursing and a discussion of the current challenges faced within the profession. It will also include how the public's perception of both those who have mental illness and those who treat it is based on the sensationalism of those who are violent, and misunderstanding of current treatments. It is imperative that mental health nurses continue to define and educate other health care professionals as well as the general public of the role of the mental health nurse and those who suffer from mental illness. Unfortunately, some of the same bias that was present in the 1930s remains today, but perhaps with perseverance and education it will not continue into the future. Keywords: mental health, psychiatric nursing, pre- licensure, post-licensure challenges, professional obstacles, public perception